Effectiveness of Perineal Massage in the Second Stage of Labor in Preventing Perineal Trauma - Suleyman Cemil Oglak; Mehmet Obut (Medical Network, 2020)
OBJECTIVE: This study was aimed to investigate the effect of perineal massage in the second stage of labor in prevention perineal traumas during childbirth. STUDY DESIGN: This observational study was conducted with 171 nulliparous women delivered by vaginally between January 2017 and May 2019. All the patients managed by the selective episiotomy principle. All the patients were divided into two groups: the perineal massage group and the control group. The perineal massage was performed during the second stage of labor until the baby's head was birth. The control group received routine labor care. In the case of threatening tears in any patient and at the preference of the midwife, mediolateral episiotomy was performed. Following childbirth, the perineum and vagina were examined for perineal tears and episiotomy by the midwives. RESULTS: The length of the second stage of labor was significantly lower in the massage group (36±19 minute) compared with the control group (46±25 minute, p=0.024). Twenty-five women (28.8%) in the massage group had intact perineum after vaginal birth, compared with five (6.0%) in the control group (p=0.003). The rate of first- and second-degree perineal tears are higher in the massage group [28 patients (32.2%) and 9 patients (10.3%), respectively] than in the control group [10 patients (11.9%) and 5 patients (6.0%), respectively, p<0.001]. The incidence of episiotomy was significantly lower in the massage group (25 patients, 28.7%) than in the control group (64 patients, 76.1%, p<0.001). CONCLUSION: Perineal massage should be considered a routine intervention to reduce the incidence of perineal trauma.